Recent Advances in Medical Therapy for Urological Cancers - Yuasa, Takeshi; Urasaki, Tetsuya; Oki, Ryosuke (Frontiers in Oncology, 2022)
Currently, the paradigm of medical treatment for patients with metastatic urological cancer is dramatically changing. Tyrosine kinase inhibitors, androgen deprivation therapy, and cytotoxic chemotherapy have been the mainstay of medical therapy for metastatic renal cell cancer, prostate cancer, and urothelial cancer, respectively. These therapeutic modalities are still important in these respective malignancies. However, immune checkpoint inhibitors targeting PD-1, PD-L1, and CTLA-4 have been rapidly introduced for treating metastatic urological cancers as they have been for other malignancies. In addition, a PARP inhibitor was just approved for the treatment of castration-resistant prostate cancer with BRCA1/2 mutations. Moreover, enfortumab vedotin, a newly designed antibody-drug conjugate (ADC) comprising a fully human monoclonal antibody conjugated to the anti-cancer agent via a protease-cleavable linker, will soon be launched in Japanese clinical practice. In this article, we introduce the agents and regimens that have just launched or will be launched in the near future in Japan. Based on their promising anti-tumor efficacy and manageable safety profile as demonstrated in clinical trials, they are expected to be successfully introduced in Japanese clinical practice. In addition, we summarize ongoing clinical trials in the Tables, and the predicted standards of care for metastatic urological cancer in 2022 are illustrated in the Figures.